High interstitial element Gr4 titanium alloy bar as well as preparation method and application thereof
By controlling specific process parameters through single-fire forging, two-fire rolling, and cold drawing, the problems of long preparation process, high cost, and uneven performance of Gr4 titanium alloy bars have been solved, resulting in high-strength and high-toughness Gr4 titanium alloy bars suitable for medical devices.
Patent Information
- Application Number
- CN202511283217.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-09
- Publication Date
- 2025-12-05
AI Technical Summary
The existing Gr4 titanium alloy bar preparation process is long and costly, making it difficult to meet the needs of industrial production. Furthermore, the high Fe and O content affects the material's strength and toughness, making it impossible to simultaneously possess both high strength and high toughness.
By employing a method of single-fire forging, two-fire rolling, and cold drawing, and controlling the deformation and temperature difference, combined with specific process parameters, especially the heating rate, annealing conditions, and cold drawing speed, high-gap element Gr4 titanium alloy bars were prepared.
We have achieved low-cost and high-efficiency preparation of Gr4 titanium alloy rods with uniform structure and excellent performance, with tensile strength ≥878MPa, yield strength ≥761MPa, elongation ≥6%, and reduction of area ≥18%, meeting the requirements of medical titanium alloys.
Smart Images

Figure CN121065611A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of titanium alloy, in particular to a high-gap-element Gr4 titanium alloy rod and a preparation method and application thereof. BACKGROUND
[0002] Under the background of the rapid development of medical technology, the field of medical oral implantation and orthopedic implantation is showing unprecedented vitality. With the increasing trend of global population aging and the continuous pursuit of people's quality of life, the market demand for oral implants and orthopedic implants is growing at an unprecedented rate. Looking back at the past five years, the annual use of global oral implants has continued to rise at a compound annual growth rate of more than 15%, and the market size of orthopedic implants has shown a strong expansion trend. This strong market demand undoubtedly puts forward more stringent and more precise requirements for the performance of implant materials, quality control and production cost.
[0003] Among the various medical implant materials, pure titanium has become one of the favored alloy materials due to its lack of Al, V and other elements that may cause allergic reactions in the human body. Among them, Gr4 pure titanium has won the widespread recognition and trust of many domestic medical manufacturers due to its excellent biocompatibility, excellent bone bonding ability and significant effect verified by long-term clinical trials. However, the existing preparation process of Gr4 pure titanium is quite long and complex, especially in the processing link, which faces many challenges. For example, in the forging process, in order to achieve the ideal organizational structure and mechanical properties of the material, it often needs to be forged repeatedly for many times, which is a typical example of complicated procedures and complex operations. The rolling process also cannot be ignored. In order to achieve precise size control and excellent surface quality, fine rolling needs to be carried out in multiple passes, which undoubtedly further prolongs the entire preparation cycle. The final precision machining link puts almost stringent requirements on the precision of processing equipment and technology to meet the high-precision use requirements of medical devices, resulting in a significant increase in processing time.
[0004] CN115069957A discloses a processing method of a new type of medical titanium alloy coronary artery drug-coated stent. TiMn medical titanium alloy is used to prepare a titanium alloy capillary tube through vacuum consumable arc furnace melting, forging, hot rolling, mechanical perforation, cold rolling, cold drawing, straightening and microsecond fiber laser engraving processes, and a polylactic acid-hydroxyacetic acid copolymer and rapamycin solution is sprayed on the surface of the titanium alloy capillary tube to form a drug coating to reduce the precipitation of harmful elements. The prepared titanium alloy has good toughness, but its mechanical strength is slightly insufficient, and the preparation process of the method is relatively long, which is not suitable for industrial production.
[0005] In summary, the methods for preparing titanium alloy materials in the prior art have the following disadvantages: 1. Low preparation efficiency, long process, high cost, not suitable for batch industrial production; 2. For high Fe, O content interstitial elements, during forging, rolling, drawing and other processing, defects such as cracking and uneven structure are prone to occur, affecting the appearance quality and use performance of the product; 3. The prepared titanium alloy material cannot have high mechanical strength and toughness.
[0006] Therefore, how to prepare a high interstitial element Gr4 titanium alloy bar with high mechanical strength and toughness in a short process by using a low-cost preparation method has become a problem to be solved. SUMMARY
[0007] In view of the above, the present application aims to provide a Gr4 titanium alloy bar and its preparation method and application, which are used to at least solve one of the following problems: (1) the preparation method of the existing Gr4 alloy bar has a long process and a complicated preparation method, which cannot meet the low-cost industrial production demand; (2) the existing pure titanium has low strength, which cannot meet the use requirements of medical titanium alloy; (3) for high Fe, O content titanium alloy, in order to avoid cracking, the forging parameters and deformation degree need to be strictly controlled, the process difficulty is increased, and it is difficult to prepare titanium alloy material on a large scale.
[0008] The purpose of the present application is mainly realized by the following technical scheme:
[0009] The present application provides a preparation method of a high interstitial element Gr4 titanium alloy bar, which comprises:
[0010] S1, performing one-pass breakdown forging on the ingot to obtain an initial blank;
[0011] S2, performing two-pass rolling on the initial blank to obtain an intermediate blank; wherein the deformation amount is controlled to be greater than 50% during one-pass rolling, and the deformation amount is controlled to be greater than 90% during two-pass rolling;
[0012] S3, performing vacuum annealing on the intermediate blank after coiling, and then performing cold drawing to obtain a Gr4 titanium alloy bar.
[0013] Further, the composition of the ingot comprises, by mass percentage: Fe: 0.25-0.32%, O: 0.25-0.35%, N≤0.01%, C≤0.02%, H≤0.002%, and the balance is Ti.
[0014] Further, the one-pass breakdown forging step comprises:
[0015] a, preheating the ingot at a first temperature, and performing first heat preservation for 180-240 min;
[0016] b. heating to a second temperature at a rate of 0.4-1.5℃ / min, and performing second heat preservation for 300-350 min;
[0017] c. upsetting, drawing and shearing the material at the second temperature, and then drawing the material at a temperature of 100-150℃.
[0018] Further, the second temperature is greater than the first temperature.
[0019] Further, the temperature difference between the first temperature and the second temperature is 120-190℃.
[0020] Further, the first temperature is 800-850℃, and the second temperature is 950-990℃.
[0021] Further, in step b, the heating rate is controlled to be 0.4-1.5℃ / min.
[0022] Further, in step c, the deformation amount of upsetting is 30-50%, and the deformation amount of drawing is 20-50%.
[0023] Further, in step S2, the initial blank is subjected to two heating times of rolling, wherein the first heating time of rolling comprises:
[0024] 1-1. heating to 830-890℃ in a resistance furnace, then loading the initial blank, and performing heat preservation for 150-210 min to obtain a heat preservation material;
[0025] 1-2. performing multi-pass rolling on the heat preservation material to a material diameter controlling the deformation amount of each pass to be N, wherein N is 20-30%, and then sawing the material rolled in the first heating time;
[0026] Further, the second heating time of rolling comprises:
[0027] 2-1. heating and heat preserving the material rolled in the first heating time in a medium frequency furnace to obtain a heat preservation material;
[0028] 2-2. performing multi-pass rolling on the heat preservation material to a material diameter controlling the deformation amount of each pass to be M, wherein M is 15-30%;
[0029] wherein M is 50-100% of N.
[0030] Further, the annealing conditions comprise: annealing the material in a vacuum degree of 10 -3 Pa and at a temperature of 650-700℃ for 60-100 min to obtain an annealed material.
[0031] Further, the deformation in the cold drawing process is 8-15%, and the speed of the cold drawing is 1-1.5 m / min.
[0032] The second aspect of the present application provides a Gr4 titanium alloy rod prepared by the method of the first aspect, wherein the Gr4 titanium alloy rod has a tensile strength of ≥878 MPa, a yield strength of ≥761 MPa, an elongation of ≥6%, and a reduction of area of ≥18%.
[0033] The third aspect of the present application provides an application of the Gr4 titanium alloy rod of the second aspect in a medical device.
[0034] Compared with the prior art, the present application can achieve at least one of the following beneficial effects:
[0035] (1) The preparation method of the Gr4 titanium alloy rod provided by the present application can prepare a medical Gr4 titanium alloy rod with excellent mechanical strength and good toughness at low cost and high efficiency through one open-die forging and elongation, two rolling and cold drawing, and control of the process parameters in the above processes.
[0036] (2) In the preparation method of the present application, the ingot with high Fe (>0.25%) and O (>0.1%) contents is forged by a specific process, specifically: the ingot is heat-treated at a first temperature and open-die forged at a second temperature under a specific heating rate (0.4-1.5 ℃ / min), and by controlling the temperature difference between the first temperature and the second temperature, the preparation process can be shortened, and a large-scale, industrialized Gr4 titanium alloy rod with uniform organization and high strength and toughness can be prepared.
[0037] (3) In the forging process of the present application, the content of Fe and O elements is accurately controlled to improve the strength of the blank, lay a foundation for obtaining a high-strength Gr4 titanium alloy rod in the subsequent process, and the temperature relationship, heating rate, deformation, annealing conditions and cold drawing speed and other process parameters in the subsequent processing process are matched with each other to avoid product cracking or excessive stress in the forging process, gradually refine the grain size of the blank, improve the uniformity of the alloy organization, and improve the comprehensive performance of the alloy by cooperating with the specific subsequent forging process, so that the Gr4 titanium alloy rod has high strength and toughness and uniform organization at the same time, and meets the requirements of medical titanium alloy rods.
[0038] (4) The Gr4 titanium alloy rod prepared by the present application has excellent mechanical properties and toughness, specifically, the tensile strength is not less than 878 MPa, the yield strength is not less than 761 MPa, the elongation is not less than 6%, and the reduction of area is not less than 18%, the performance and precision level are high, can reach the medical grade standard, and the performance stability is high, the Cv value is not less than 5.
[0039] Other features and advantages of the present application will be set forth in the description that follows, and in part will become apparent to those skilled in the art upon examination of the following or can be learned by practice of the application. The objects and other advantages of the application can be realized and attained by the structure particularly pointed out in the written description and claims hereof as well as the appended drawings. BRIEF DESCRIPTION OF DRAWINGS
[0040] The accompanying drawings, which are included to provide a further understanding of the application and are incorporated in and constitute a part of this application, illustrate embodiments of the application and together with the description serve to explain the principles of the application. In the drawings:
[0041] Figure 1 Metallographic structure of Gr4 titanium alloy bar with a specification of Φ5mm;
[0042] Figure 2 Metallographic structure of Gr4 titanium alloy bar with a specification of Φ5.25mm;
[0043] Figure 3 Metallographic structure of Gr4 titanium alloy bar with a specification of Φ5.6mm. DETAILED DESCRIPTION
[0044] The preferred embodiments of the present application will be described in detail below with reference to the drawings, wherein the drawings constitute a part of this application and serve to explain the principles of the embodiments of the present application together with the description.
[0045] There are many preparation methods for Gr4 titanium alloy materials, but the preparation processes are relatively long, and the preparation methods are complicated. For Gr4 titanium alloy with high interstitial elements (mainly high Fe and high O content), the existing technology cannot simultaneously meet the performance requirements of high strength and high toughness and the industrial production requirements. Since the high Fe and O content increases the difficulty of the smelting process and affects the performance of the alloy, such as reducing the toughness of the alloy, the use requirements of medical titanium alloy cannot be met. Therefore, it is urgent to develop a short-process preparation and large-scale production of Gr4 bar with high Fe and high O content, which can ensure excellent performance of the material and improve production efficiency and reasonably control cost.
[0046] The present application provides a processing method of Gr4 titanium alloy bar with high interstitial elements, comprising:
[0047] S1, performing one-pass blooming forging on the ingot to obtain an initial billet;
[0048] S2, performing two-pass rolling on the initial billet to obtain an intermediate billet; wherein the deformation amount is controlled to be greater than 50% in the one-pass rolling process, and the deformation amount is controlled to be greater than 90% in the two-pass rolling process;
[0049] S3, performing vacuum annealing on the intermediate billet after coiling, and then performing cold drawing to obtain the Gr4 titanium alloy bar.
[0050] Specifically, in the step S1, the composition of the ingot includes, in percentage by mass: Fe: 0.25-0.32%, O: 0.25-0.35%, N≤0.01%, C≤0.02%, H≤0.002%, and the balance is Ti.
[0051] Specifically, in the application, the specification of the ingot can be
[0052] Specifically, considering that high Fe and high O contents will affect the strength and toughness of the alloy, in the ingot, Fe: 0.25-0.32%, O: 0.25-0.35%, if the content of Fe is less than 0.25% or the content of O is less than 0.25%, the strength will decrease significantly, if the content of Fe is greater than 0.32% or the content of O is greater than 0.35%, the toughness of the alloy is difficult to improve in the subsequent processing process, and it is easy to crack in the processing process.
[0053] Exemplarily, the content of Fe can be 0.25%, 0.26%, 0.27%, 0.28%, 0.3%, 0.32%, and a range composed of any two of the above values, preferably 0.28-0.3%.
[0054] Exemplarily, the content of O can be 0.25%, 0.26%, 0.27%, 0.28%, 0.3%, 0.32%, 0.35%, and a range composed of any two of the above values, preferably 0.3-0.32%.
[0055] Specifically, the Gr4 titanium alloy bar with a specification of is taken as an example, in the step S1, the step of one-time open die forging includes:
[0056] a. preheat the ingot at a first temperature, and perform first heat preservation for 180-240 min;
[0057] b. increase the temperature to a second temperature at a rate of 0.4-1.5 ℃ / min, and perform second heat preservation for 300-350 min;
[0058] c. one-up, one-down, and one-cut on the above material at the second temperature, and then cool to 100-150 ℃, and elongate.
[0059] In the application, considering overcoming the problem of difficult forging process caused by high Fe and O contents, the second temperature is preferably higher than the first temperature.
[0060] Further, considering shortening the preparation process without affecting the quality of the finished product, the temperature difference between the first temperature and the second temperature is controlled to be 120-190 ℃.
[0061] In the present application, the temperature difference between the first temperature and the second temperature can be 120℃, 125℃, 130℃, 140℃, 145℃, 150℃, 160℃, 165℃, 170℃, 178℃, 180℃, 190℃, and a range formed by any two of the above values, preferably 140-190℃.
[0062] In the present application, when the temperature difference between the first temperature and the second temperature is 140-190℃, the performance stability of the alloy product can be ensured, especially the stability of the alloy strength, the performance of the products in the same batch is consistent, and the problem of poor reproducibility is avoided, which affects the industrial production and application.
[0063] Specifically, the first temperature is 800-850℃, and the second temperature is 950-990℃, so that only one forging can be performed, the processing flow can be further shortened without affecting the quality of the finished product, and the product performance stability is improved.
[0064] In the present application, in step b, the heating rate is controlled to be 0.4-1.5℃ / min, which can make the temperature uniform, ensure uniform heating of the entire blank, thereby promoting uniform recrystallization process, helping to refine the grain, making the grain size more uniform and consistent, and significantly improving the strength and toughness of the titanium alloy bar.
[0065] In the present application, the heating rate can be 0.4℃ / min, 0.5℃ / min, 0.6℃ / min, 0.7℃ / min, 0.8℃ / min, 0.9℃ / min, 1℃ / min, 1.05℃ / min, 1.08℃ / min, 1.2℃ / min, 1.25℃ / min, 1.3℃ / min, 1.5℃ / min, and a range formed by any two of the above values, preferably 1.05-1.5%.
[0066] The inventors have found through a large number of studies that for the specific material and specific process in the present application, controlling the deformation amount of the "upsetting" to be 30-50% can make the grains completely broken during the cogging forging process, providing a basis for subsequent grain refinement. For example, it can be 30%, 35%, 40%, 45%, 50%, and a range formed by any two of the above values, preferably 40-50%.
[0067] Similarly, for the specific material and specific process in the present application, controlling the deformation amount of the "drawing" to be 20-50% and cooperating with the deformation amount of the above "upsetting" can realize multi-directional and uniform deformation and improve the uniformity of the microstructure of the finished product.
[0068] In the present application, for the specific material and specific process in the present application, only when the processes of "upsetting" and "drawing" are matched with each other, and the deformation amounts of the respective processes meet the above range respectively, can the alloy strengthening and toughening and the uniformity of the structure be realized. When the deformation amount of any one of the above "upsetting" and "drawing" processes is less than the lower limit value, the material structure will be non-uniform due to insufficient deformation, and in order to make the material structure uniform, the number of heating times is increased, resulting in a longer process and higher cost. When the deformation amount of any one of the processes is greater than the upper limit value, micro-cracks will appear in the material, affecting the product quality.
[0069] In the present application, specifically, in step c, the role or purpose of the return to the furnace is to supplement the temperature.
[0070] It can be understood that in step c, the drawing specification can be performed according to the target specification, for example, for the titanium alloy bar in the present application , the drawing in step c is to
[0071] In the present application, after the one-time breakdown forging, the initial billet is further subjected to chamfering and splitting, and full grinding.
[0072] In the present application, in step S2, the initial billet is subjected to two-time rolling, which can gradually refine the grain size of the billet. Specifically, the first-time rolling includes the following steps:
[0073] 1-1, in the resistance furnace, the temperature is raised to 830-890 DEG C, then the initial billet is loaded, and the temperature is kept for 150-210 min to obtain a temperature-maintained material;
[0074] 1-2, the temperature-maintained material is subjected to multi-pass rolling to a material diameter of 100-105 mm, and the deformation amount N of single pass is controlled, and then the material rolled in the first time is sawn.
[0075] In the present application, before the first-time rolling, the initial billet is subjected to heating in the resistance furnace, which can ensure the economy of heating, reduce the equipment cost, and further, keeping the temperature at 830-890 DEG C for 150-210 min can ensure temperature homogenization, which is helpful to uniform occurrence of structure phase change in the rolling process, avoids incomplete or non-uniform phase change in local area, and improves the uniformity of the structure of the titanium alloy.
[0076] In the present application, specifically, the rolling times of the temperature-maintained material are not particularly limited, as long as the diameter is 100-105 mm, and the deformation amount N of single pass rolling is controlled to be 20-30%, so that the effect of fine grain and no cracking can be achieved.
[0077] In the present application, considering that if the length is too long after the billet is drawn, it will be not conducive to subsequent rolling operation, the first fire rolled material is sawn, and the sawing length is 4000-6000mm.
[0078] The method of the present application further comprises skinning overhauling the first fire rolled material.
[0079] In the present application, the second fire rolling comprises the following steps:
[0080] 2-1, heating and heat-insulating the first fire rolled material in the intermediate frequency furnace to obtain heat-insulated material;
[0081] 2-2, rolling the heat-insulated material in multiple passes to a material diameter of 11-11.5mm. The deformation amount of each pass is controlled to be M, and then the second fire rolled material is disc round overhauled.
[0082] In the present application, specifically, in step 2-1, considering that the intermediate frequency furnace has high heating efficiency and fast heating speed, the process can be shortened, and the heating time is preferably 8-15min. The inventors have found through a large number of studies that controlling the heating time to be 8-15min can ensure that the heating temperature is 800-850℃, and the material is heated more uniformly. Further, when the heat-insulating time is less than 8min, the material will be heated unevenly, the core temperature of the material will be less than 800℃, resulting in uncoordinated deformation during subsequent processing and causing the billet to crack, and when the heat-insulating time is greater than 15min, it will promote rapid grain growth, which is not conducive to refining the grains.
[0083] In the present application, specifically, in step 2-2, the heat-insulated material in step 2-1 is rolled to a diameter of 11-11.5mm, and the deformation amount M of each pass is controlled to be 15-30%, so that a uniform billet can be prepared for the next drawing, and the final product organization is more uniform.
[0084] According to a preferred embodiment of the present application, M is controlled to be 50-100% of N, which can cooperate with the deformation amount of two rolling passes, one fire rolling has a larger deformation amount to avoid defects such as cracks and holes, and two fire rolling can further optimize the strength of the billet at a relatively small deformation amount, which helps to maintain fine grain structure, prevent grain growth, and thus maintain high strength. Avoid cracking. The deformation amount of two rolling passes meets the above parameters, which can effectively refine the grains, optimize the microstructure, improve the strength and toughness of the material, and reduce the generation of defects. By reasonably controlling the deformation amount of each rolling pass, a balance between strength and plasticity can be achieved, the overall performance of the titanium alloy is improved to ensure the uniformity of the microstructure, the grains are refined, the phase transition is promoted, the strength and toughness are improved, and the generation of internal defects of the material is avoided.
[0085] In the present application, M can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 90%, 100% of N, and preferably 60-90%.
[0086] In the present application, during the first fire rolling, the material is kept in the resistance furnace, and during the second fire rolling, the material is kept in the intermediate frequency furnace, so that the heating efficiency can be improved, the production cost can be greatly reduced, and the process can be shortened under the premise of ensuring high uniformity of the material organization.
[0087] In the present application, the material temperature and the holding time before the second fire rolling are less than the material temperature and the holding time before the first fire rolling, because the second fire needs to control the two-phase organization ratio of the alloy, so that the strength and toughness of the alloy product can be ensured.
[0088] In the present application, specifically, in order to avoid oxidation of the alloy, vacuum annealing is performed after the intermediate blank disc is obtained. Preferably, the annealing conditions include: annealing for 60-100 min at a temperature of 650-700℃ under a vacuum degree of 10 -3 Pa.
[0089] In the present application, the inventors have found through a large number of studies that when the annealing conditions meet the above range, the alloy grains can be fully recrystallized, if the annealing temperature is lower than 650℃, the crystallization is insufficient, resulting in excessive residual stress of part of the organization, subsequent deformation is not coordinated, and the toughness decreases, if the annealing temperature is higher than 700℃, the grains abnormally grow, resulting in a decrease in the strength of the alloy. In the present application, if annealing is not performed, the residual stress will be too high, and the alloy will directly break during subsequent processing.
[0090] In the present application, in step S3, multiple passes of cold drawing can be performed to obtain the required specification But the deformation amount in the single-pass cold drawing process needs to be controlled to be 8-15%. In this way, the deformation of the alloy can be uniformly controlled, the Gr4 titanium alloy with uniform organization and refined grains can be obtained, and the strength and toughness of the Gr4 titanium alloy can be improved.
[0091] In the present application, considering that too fast or too slow deformation speed is not conducive to industrialized production, the speed of single-pass cold drawing is controlled to be 1-1.5 m / min, so that the material can be deformed at a relatively stable and suitable speed, the uniformity of the alloy organization can be improved, the foundation for large-scale and industrialized production can be laid, and the production efficiency can be improved.
[0092] The second aspect of the present application provides a Gr4 titanium alloy rod prepared by the method of the first aspect.
[0093] In this invention, the Gr4 titanium alloy bar has both excellent strength and toughness. Specifically, the tensile strength of the Gr4 titanium alloy bar is ≥878MPa, the yield strength is ≥761MPa, the elongation is ≥6%, the reduction of area is ≥18%, and the Cv value is not greater than 5.
[0094] Preferably, the Gr4 titanium alloy bar has a tensile strength ≥1000MPa, a yield strength ≥950MPa, an elongation ≥9%, a reduction of area ≥30%, and a Cv value not greater than 1.
[0095] A third aspect of this invention provides an application of the Gr4 titanium alloy rod described in the second aspect in medical devices. In this invention, the Gr4 titanium alloy rod possesses both high strength and high toughness. Specifically, the high strength is manifested in high tensile strength and yield strength, and the high toughness is manifested in high elongation and reduction of area. This meets the requirements for the application of the Gr4 titanium alloy rod in medical devices, specifically as archwires in the oral cavity.
[0096] The advantages of precise control of process parameters according to the present invention are demonstrated below with specific embodiments and comparative examples. In the following embodiments and comparative examples,
[0097] The tensile strength and yield strength of TiZr alloy wire were tested according to the method of GB / T 228.1-2010;
[0098] The elongation and cross-sectional shrinkage of TiZr alloy wire were tested according to the method of GB / T 228.1-2010;
[0099] The Cv value is used to evaluate the consistency of TiZr alloy wire, also known as the coefficient of variation. In this invention, the same raw material is forged 5 times under the same process conditions, and then the standard deviation and average value of tensile strength are calculated. The calculation formula is: Cv = (standard deviation of performance parameter / average value) × 100%.
[0100] Example 1
[0101] This embodiment is used to illustrate the specifications. Gr4 titanium alloy rods and their preparation methods
[0102] S1, will Gr4 ingots (composition: Fe: 0.3%; O: 0.32%; unavoidable impurities (N: 0.0036%; C: 0.005%; H: 0.001%); balance Ti) were preheated at 850℃ and held for 210 min, then heated to 990℃ (heating rate: 1.5℃ / min) and held for 300 min.
[0103] The above material is subjected to one upsetting operation at 990℃ with a controlled deformation of 40%, then elongated and cut, then the cut material is returned to the original furnace and kept at 850℃ for 60min, and finally elongated to Then, chamfering and full grinding are performed to obtain the initial billet.
[0104] S2-1, in an electric resistance furnace, the temperature is raised to 850℃ at a rate of 1.5℃ / min, then the initial billet is loaded and kept for 150min to obtain the holding material, and the holding material is rolled for 3-5 passes to a material diameter of The deformation N of a single pass is controlled to be 20%, then the material rolled in the first fire is sawed to a length of 4000mm, and then the sawed material is skinned and repaired;
[0105] S2-2, in a medium frequency furnace, the material rolled in the first fire is heated to 850℃ and kept for 150min to obtain the holding material, and the holding material is rolled for 5 passes to a material diameter of The deformation M of a single pass is controlled to be 15% to obtain the intermediate billet, wherein M is 75% of N;
[0106] S3, the above intermediate billet is coiled and then vacuum annealed at 10 -3 Pa, 700℃ for 60min, and then the material is cold drawn to Φ5.00mm at a speed of 1m / min to obtain Gr4 titanium alloy rod A1.
[0107] Example 2-3
[0108] According to the method of Example 1, except that the intermediate billet after annealing is cold drawn to Φ5.25mm and Φ5.6mm.
[0109] The performance results of Gr4 titanium alloy rods A2 and A3 are shown in Table 1, and the morphology is shown in Figures 2-3 It can be seen from Figure 2 , Figure 3 that the alloys all have fine-grained structure, and the mechanical properties all meet the medical standards.
[0110] Example 4
[0111] According to the method of Example 1, except that in step S2-1, the deformation N is controlled to be 30% so that M is 50% of N. The performance results of the prepared Gr4 titanium alloy rod A4 are shown in Table 1.
[0112] Example 5
[0113] The method of Example 1 was followed, except that in Step S2-2, the amount of deformation M was controlled to be 20%, so that M was 100% of N. The properties of the Gr4 titanium alloy bar A5 produced are shown in Table 1.
[0114] Example 6
[0115] The method of Example 1 was followed, except that in Step S1, the Gr4 ingot (having the same composition as Example 1) was preheated at 850°C for 210 min, and then heated to 990°C at a rate of 0.8°C / min for 300 min. The other steps were the same as Example 1. The properties of the Gr4 titanium alloy bar A6 produced are shown in Table 1.
[0116] Example 7
[0117] The method of Example 1 was followed, except that in Step S1, the Gr4 ingot (having the same composition as Example 1) was preheated at 800°C for 210 min, and then heated to 990°C at a rate of 1.05°C / min for 300 min. The other steps were the same as Example 1. The properties of the Gr4 titanium alloy bar A7 produced are shown in Table 1.
[0118] Example 8
[0119] The method of Example 1 was followed, except that in Step S1, the amount of deformation during upsetting was controlled to be 30%. The other steps were the same as Example 1. The properties of the Gr4 titanium alloy bar A8 produced are shown in Table 1.
[0120] Example 9
[0121] The method of Example 1 was followed, except that the temperature during vacuum annealing was 700°C. The other steps were the same as Example 1. The properties of the Gr4 titanium alloy bar A9 produced are shown in Table 1.
[0122] Example 10
[0123] The method of Example 1 was followed, except that in Step S3, the speed of cold drawing was controlled to be 1.5 m / min. The other steps were the same as Example 1. The properties of the Gr4 titanium alloy bar A10 produced are shown in Table 1.
[0124] Example 11
[0125] The method of Example 1 was followed, except that the ingot had the following composition: Fe 0.2%; O 0.2%; N 0.0036%; C 0.005%; H 0.001%, with the balance being Ti. The other steps were the same as in Example 1, and the properties of the Gr4 titanium alloy bar A11 produced are shown in Table 1.
[0126] Example 12
[0127] The method of Example 1 was followed, except that the ingot had the following composition: Fe 0.4%; O 0.5%; N 0.0038%; C 0.02%; H 0.001%, with the balance being Ti. The other steps were the same as in Example 1, and the properties of the Gr4 titanium alloy bar A12 produced are shown in Table 1.
[0128] Example 13
[0129] The method of Example 1 was followed, except that in step S2-1, the initial billet was heated to 850°C at a rate of 1.5°C / min in an electric resistance furnace, and then the initial billet was charged and held for 150 min to obtain a holding material.
[0130] In step S2-2, the first fire-rolled material was heated to 950°C in an intermediate frequency furnace and held for 300 min to obtain a holding material. The remaining steps were the same as in Example 1, and the properties of the Gr4 titanium alloy bar A12 produced are shown in Table 1.
[0131] Comparative Example 1
[0132] The method of Example 1 was followed, except that in step S3, instead of vacuum annealing, the intermediate billet obtained in step S2-2 was directly cold-drawn to Φ5.00 mm to obtain a Gr4 titanium alloy bar D1, and the mechanical properties are shown in Table 1.
[0133] Comparative Example 2
[0134] The method of Example 1 was followed, except that an additional rolling step was added, i.e., step S2-3: the second fire-rolled material was heated to 850°C in an intermediate frequency furnace and held for 150 min to obtain a holding material, and the holding material was rolled for 2 passes, with the deformation amount of each pass being controlled to be 15%.
[0135] Table 1
[0136]
[0137] The above results show that the Gr4 titanium alloy rod prepared by the method provided by the application has significantly improved mechanical strength under the premise of ensuring toughness. Specifically, the elongation is not less than 6%, the reduction of area is not less than 19%, the tensile strength is not less than 870 MPa, the yield strength is not less than 760 MPa, and the strength Cv value is not greater than 5.
[0138] The embodiments 1-3 and 7 further satisfying the preferred scheme obtain obviously better effects. Specifically, the elongation is not less than 9%, the reduction of area is not less than 33%, the tensile strength is not less than 1000 MPa, the yield strength is not less than 980 MPa, and the strength Cv value is not greater than 1.
[0139] Figures 1-3 The metallographic photos of the Gr4 titanium alloy rods prepared in the embodiments 1-3 are shown in FIGS. 1-3, respectively. As shown in the figures, the transverse and longitudinal organizations of the alloy wires prepared in the embodiments 1-3 are relatively uniform, showing a uniform and fine grain structure, and the phase composition is uniform without obvious phase separation or segregation.
[0140] The above description is only the preferred specific implementation of the application, but the protection scope of the application is not limited to this. Any changes or replacements within the technical range disclosed by the application can be easily thought of by those skilled in the art, and should be covered in the protection scope of the application.
Claims
1. A method of producing a high interstitial element Gr4 titanium alloy bar material, characterized by, The preparation method comprises: S1, one fire once open forging of ingot, to obtain the initial billet; S2, the initial billet is rolled twice, to obtain the intermediate billet; wherein, the deformation amount is controlled to be greater than 50% in the first fire rolling process, and the deformation amount is controlled to be greater than 90% in the second fire rolling process; S3, the intermediate billet is coiled and then vacuum annealed, and then cold drawn to obtain the Gr4 titanium alloy rod.
2. The production method according to claim 1, characterized by, The composition of the ingot comprises, in mass percentage: Fe: 0.25-0.32%, O: 0.25-0.35%, N≤0.01%, C≤0.02%, H≤0.002%, and the balance is Ti.
3. The preparation method according to claim 1, characterized in that, The step of one fire once open forging comprises: a, preheating the ingot at a first temperature, and performing first heat preservation for 180-240 min; b, heating to a second temperature at a rate of 0.4-1.5 ℃ / min, and performing second heat preservation for 300-350 min; c, one upsetting, one drawing, and one cutting of the material at the second temperature, and then cooling to 100-150 ℃ and drawing.
4. The production method according to claim 3, characterized by, The second temperature is greater than the first temperature.
5. The preparation method according to claim 3, characterized in that, The temperature difference between the first temperature and the second temperature is 120-190 ℃; And / or, the first temperature is 800-850 ℃, and the second temperature is 950-990 ℃; And / or, in step b, the heating rate is controlled to be 0.4-1.5 ℃ / min; And / or, in step c, the deformation amount of the upsetting is 30-50%, and the deformation amount of the drawing is 20-50%.
6. The method of claim 1, wherein, In step S2, the initial billet is rolled twice, wherein the first fire rolling comprises: 1-1, heating to 830-890 ℃ in a resistance furnace, then loading the initial billet, and heat preserving for 150-210 min to obtain the heat preserved material; 1-2, multi-pass rolling the heat preserved material to a material diameter of φ100-105 mm, controlling the deformation amount N of each pass to be 20-30%, and then sawing the first fire rolled material.
7. The production method according to claim 6, wherein In the second fire rolling, the second fire rolling comprises: 2-1, heating and heat preserving the first fire rolled material in a medium frequency furnace to obtain the heat preserved material; 2-2, multi-pass rolling the heat preserved material to a material diameter of φ11-11.5 mm, controlling the deformation amount M of each pass to be 15-30%; Wherein, the M is 50-100% of the N.
8. The method of claim 1, wherein, The annealing conditions include: annealing the material at a temperature of 650-700℃ for 60-100min under a vacuum of 10 - 3 Pa to obtain an annealed material; And / or, the deformation amount in the cold drawing process is 8-15%, and the speed of the cold drawing is 1-1.5 m / min.
9. A Gr4 titanium alloy bar produced by the method of any one of claims 1 to 8, characterised in that, The tensile strength of the Gr4 titanium alloy rod is ≥878 MPa, the yield strength is ≥761 MPa, the elongation is ≥6%, and the reduction of area is ≥18%.
10. The Gr4 titanium alloy rod of claim 9 is applied in medical devices.